A Studi on High Plant Systems Course with Active Learning in Higher Education Through Outdoor Learning to Increase Student Learning Activities - Anwari Adi Nugroho; Nur Rokhimah Hanik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Biology learning especially high plant system courses needs to be applied to active learning centered on the student (Active Learning In Higher Education) to enhance the students' learning activities so that the quality of learning for the better. Outdoor Learning is one of the active learning invites students to learn outside of the classroom by exploring the surrounding environment. This research aims to improve the students' learning activities in the course of high plant systems through the application of Outdoor Learning. The experiment was conducted on students of fourth semester Biology Education Program Faculty of Teacher Training and Education University of Veteran Bangun Nusantara Sukoharjo Academic Year 2014/2015. This research is a measure that consists three cycles and each cycle consists of four phases: planning, action, observation, and reflection. The technique of collecting data through observation using observation sheet to measure students' learning activities. Data analysis was performed in a descriptive study using the technique of the percentage of students with an analysis of the level of activity in the learning process. Targeted research is an increase in activity score learn every cycle and meet the performance indicators that have been defined.The results showed that the Outdoor Learning can improve students' learning activities. The increase occurred in the learning activities of students from the first cycle to the second cycle of 4.5% and from cycle II to cycle III by 2.2%. Score each learning activity indicator also has met predetermined performance indicators.